PENDIRIAN RUMAH IBADAT PASCA PBM NOMOR 9 DAN 8 TAHUN 2006 DAN KERUKUNAN UMAT BERAGAMA (Kasus Pendirian Gereja di Kota Bandung, Jawa Barat) - Anik Farida (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2017)
The establishment of house of worship is one of the crucial issues in the harmony of religious life in Indonesia. Some research have been conducted on the case of the construction of houses of worship, but it use the civic pluralism or human rights perspectives. This paper presents the results of research on the case of the construction of houses of worship, namely the church in Bandung, West Java, with conflict management perspective. This study was designed as a case study, by conducting interviews and observations as well as reviewing documents with conflict management perspectives and regulations on the establishment of houses of worship, by examining the elements of the community involved in the process of building houses of worship and the social mechanisms undertaken. The results of this study indicate that the openness and communication between elements involved in the construction of houses of worship, as well as the process of socialization became an important factor in the establishment of the church, even in places where religious worshipers became ‘minorities.’ Social mechanisms or socialization between elements involved in the construction by itself will strengthen the harmony of religious life.